An Improved Force-Angle Stability Margin for Radial Symmetrical Hexapod Robot Subject to Dynamic Effects. (20th May 2015) - Long, Shidong; Xin, Guiyang; Deng, Hua; Zhong, Guoliang
This paper presents a study on stability monitoring for a radial symmetrical hexapod robot under dynamic conditions. The force-angle stability margin (FASM) measure method has been chosen as the stability criterion. This is because it is suitable for the stability analysis, in terms of external forces or manipulator loads acting on the body. Considering that a radial symmetrical hexapod robot can tumble along the contact point besides tip-over axis, this paper proposes an improved FASM measure method. Furthermore, it provides the method for calculating the stability angle of contact point and simplifies the algorithm of FASM. To verify the improved FASM measure method, three potential dynamic situations have been simulated. The simulation results confirm that, under dynamic conditions, the improved FASM is efficient, simple in terms of calculation cost and sensitive to manipulator loads and external disturbances. This means it has practical value in on-line controllers.